The Effect of Wrist Flexibility and Self-Confidence on Basketball Shooting Free Throw Results - Agung Saepuloh; Rony Muhammad Rizal; Suhada M.Pd (Journal of Physical and Outdoor Education, 2026)
This study aims to determine the effect of wrist flexibility and self-confidence on free throw performance in basketball among athletes of the Gotte Basketball Club. The method used was quantitative descriptive with a total sampling approach involving 12 athletes from KU 20. The research instruments consisted of a wrist flexibility test, a self-confidence questionnaire, and a free throw skill test. The results of simple linear regression analysis indicate that wrist flexibility has a significant influence on free throw performance with an R² value of 0.684 and a p-value of 0.0009. Meanwhile, self-confidence has a positive but non-significant influence (R² = 0.203; p-value = 0.141). Multiple regression analysis showed that both variables together explained 73% of the variation in free throw outcomes, but only wrist flexibility remained significant (p = 0.0023). These findings indicate that wrist flexibility is the dominant factor in supporting free throw accuracy, while self-confidence has not yet shown a strong influence in the context of training. This study suggests that coaches should emphasize flexibility training and create training situations that stimulate psychological pressure to enhance athletes' self-confidence.